2010
DOI: 10.1590/s0104-11692010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of impaired spirituality in patients with chronic renal disease

Abstract: This study aimed to identify and validate the defining characteristics of the nursing diagnosis Impaired spirituality. The methodological framework proposed by Fehring for the clinical validation of nursing diagnosis was used. The investigation was carried out in a dialysis clinic and had as participants 120 patients with chronic renal disease. Data were collected by two expert nurses, through interviews. The prevalence of the nursing diagnosis Impaired spirituality in the sample was 27.5%. It was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
3
39
0
Order By: Relevance
“…In terms of measured aspects of these dimensions, the findings indicated that those patients have a high mean level of a close, deep, and satisfied relationship with God, getting strength and support from God, praying, remembrance of Allah (dhikr), and reading from the Qur'an. Several studies similar to the current one reported high levels of religious wellbeing and religiosity (Chaves et al, 2010;Tanyi & Werner, 2007) The scores obtained from the DASS-21, DS, AS, and SS revealed that these hemodialysis patients had mean scores of moderate depression (32.5% of patients had severe to extremely severe depression), severe anxiety (54.1% had severe to extremely severe anxiety), and mild to moderate stress (23.4% had severe to extremely severe stress). These findings are consistent with other studies using a sample of Jordanian hemodialysis patients (Nabolsi et al, 2015) and various Western samples of hemodialysis patients (Chilcot et al, 2011;Cukor et al, 2008).…”
Section: Levels Of Spiritual Existential and Religious Wellbeing Rsupporting
confidence: 73%
“…In terms of measured aspects of these dimensions, the findings indicated that those patients have a high mean level of a close, deep, and satisfied relationship with God, getting strength and support from God, praying, remembrance of Allah (dhikr), and reading from the Qur'an. Several studies similar to the current one reported high levels of religious wellbeing and religiosity (Chaves et al, 2010;Tanyi & Werner, 2007) The scores obtained from the DASS-21, DS, AS, and SS revealed that these hemodialysis patients had mean scores of moderate depression (32.5% of patients had severe to extremely severe depression), severe anxiety (54.1% had severe to extremely severe anxiety), and mild to moderate stress (23.4% had severe to extremely severe stress). These findings are consistent with other studies using a sample of Jordanian hemodialysis patients (Nabolsi et al, 2015) and various Western samples of hemodialysis patients (Chilcot et al, 2011;Cukor et al, 2008).…”
Section: Levels Of Spiritual Existential and Religious Wellbeing Rsupporting
confidence: 73%
“…8 Patients undergoing hemodialysis face limitations in their daily lives and also experience many losses and biopsychosocial changes, such as the loss of health (at a physiological and biochemical level), anemia, loss of physical, cognitive and sexual capacity, loss of the capacity to work and to perform other tasks and functions, and dependency on medical treatment and renal therapy, in addition to physical changes and body image, and diet and fluid restrictions associated with the treatment. 9 Therefore, those living with CKD must adapt not only to the disease and its treatment, but also to the physiological, psychosocial and spiritual problems arising from this process, 10 which are situations that directly impact patients' QOL.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of nursing diagnoses plays a critical role, such as the nursing diagnosis of spiritual distress, since nurses play a significant role in alleviating the patients´suffering. In this regard, Caldeira et al (2017) conducted a clinical validation of the nursing diagnosis of spiritual distress in cancer patients undergoing chemotherapy, while Chaves et al (2010) validated impaired spirituality in patients with chronic renal disease. However, the greatest obstacle for the validation of nursing diagnoses is the methodology, which can be complex and require broad knowledge in the areas of epidemiology and biostatistics (Lopes et al 2013).…”
Section: Discussionmentioning
confidence: 99%